2022
DOI: 10.4240/wjgs.v14.i10.1141
|View full text |Cite
|
Sign up to set email alerts
|

Topological approach of liver segmentation based on 3D visualization technology in surgical planning for split liver transplantation

Abstract: BACKGROUND Split liver transplantation (SLT) is a complex procedure. The left-lateral and right tri-segment splits are the most common surgical approaches and are based on the Couinaud liver segmentation theory. Notably, the liver surface following right tri-segment splits may exhibit different degrees of ischemic changes related to the destruction of the local portal vein blood flow topology. There is currently no consensus on preoperative evaluation and predictive strategy for hepatic segmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Additionally, adherence to conventional criteria for SLT, such as the graft-to-recipient weight ratio (GRWR), is crucial. Typically, a GRWR greater than 1% for adults[ 8 , 15 ] and between 2% to 4% for children is recommended. In our study, all the 25 recipients of SLT met these criteria and did not experience postoperative complications such as large-for-size or small-for-size graft syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, adherence to conventional criteria for SLT, such as the graft-to-recipient weight ratio (GRWR), is crucial. Typically, a GRWR greater than 1% for adults[ 8 , 15 ] and between 2% to 4% for children is recommended. In our study, all the 25 recipients of SLT met these criteria and did not experience postoperative complications such as large-for-size or small-for-size graft syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Reyes et al [ 17 ] previously reported that the survival rates of recipients undergoing in-situ and ex-vivo liver splitting were comparable and similar to the survival rates of WLT recipients, in line with the findings of our study. Our literature review revealed that the majority of transplant centers have a preference for the in-situ liver-splitting approach[ 8 , 12 , 18 ]. In-situ liver splitting involves performing the procedure within the donor’s body for liver procurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation